Photoelastic colloidal gel for a high-sensitivity strain sensor. (2nd March 2018) - Pan, Hui; Chen, Zhixin; Zhu, Shenmin; Jiang, Chun; Zhang, Di
Abstract: Nanoparticles, having the ability to self-assemble into an ordered structure in their suspensions, analogous to liquid crystals, have attracted extensive attention. Herein, we report a new type of colloidal gel with an ordered crystal structure assembled from 1D and 2D nanoparticles. The material has high elasticity and, more interestingly, it shows significant photoelasticity. Its refractive index can be tuned under external stress and exhibits an ultra-wide dynamic range (Δ n ) of the order of 10 −2 . Due to the large Δ n, the material shows an extremely high strain sensibility of 720 nm/ ε, an order of magnitude higher than the reported ones.